CONTRIBUTIONS OF PSYCHOLOGY IN THE EARLY TREATMENT OF AUTISM: AN ANALYSIS OF THE DENVER MODEL - Ferreira, Yone Monteiro; Gomes, Lucas Silva; Santos, Lizandra Lima; Souza, Heden Robson Monteiro; Rodrigues, Alex Bruno Lobato; Faustino, Cleidjane Gomes; Viana, Jennepher da Cruz; Morais, Edmilson dos Santos (Seven Editora, 2025)
Autism Spectrum Disorder (ASD) is a condition characterized by significant changes in social, communicative, and behavioral development, requiring specialized and early therapeutic interventions. Among the approaches that have stood out in the scientific literature, the Early Start Denver Model (ESDM) emerges as an evidence-based proposal, integrating principles of child development, applied behavior analysis, and naturalistic practices. Psychology plays a central role in this context, by understanding the specific needs of child development and articulating intervention strategies that enhance the cognitive, social and communicative skills of children with ASD. This study aimed to analyze the efficacy of ESDM in the development of children with ASD, especially those who are without a confirmed diagnosis or awaiting specialized treatment. To this end, a descriptive research was carried out, with a qualitative approach, through a bibliographic review in national and international databases, such as PePSIC, SciELO and PubMed, as well as institutional repositories and government data. The methodological choice is justified by the need to gather and synthesize the existing evidence on the effects of ESDM in different contexts, expanding the understanding of the model’s applicability in different realities. The results showed that early intervention with ESDM promotes significant benefits for the overall development of children with ASD, even when applied in low-intensity contexts, such as school and family environments. Among the gains observed are the improvement of expressive and receptive language, advances in cognition, adaptive behavior and social interaction, as well as the reduction in the severity of symptoms characteristic of the autism spectrum. Such findings corroborate the importance of public policies that favor early diagnosis and the offer of specialized treatments, reinforcing the role of Psychology in the design of therapeutic practices that respect the specificities of child development. It is concluded that ESDM is an effective tool in the context of early intervention, being fundamental to minimize the impacts of ASD and promote the quality of life of children and their families. It is also recommended that additional studies be carried out in Brazil, in order to strengthen the national empirical base and expand access to evidence-based practices in the field of Developmental Psychology. DOI: https://doi.org/10.56238/sevened2025.021-008